Social & cultural antropology: A very short introduction - Just, Peter; Monaghan, John (Oxford Oxford university press, 2000)
"If you want to know what anthropology is, look at what anthropologists do," write the authors of Social and Cultural Anthropology: A Very Short Introduction. This engaging overview of the field combines an accessible account of some of the discipline's guiding principles and methodology with abundant examples and illustrations of anthropologists at work.Peter Just and John Monaghan begin by discussing anthropology's most important contributions to modern thought: its investigation of culture as a distinctively human characteristic, its doctrine of cultural relativism, and its methodology of fieldwork and ethnography. Drawing on examples from their own fieldwork in Indonesia and Mesoamerica, they examine specific ways in which social and cultural anthropology have advanced our understanding of human society and culture. Including an assessment of anthropology's present position, and a look forward to its likely future, Social and Cultural Anthropology will make fascinating reading for anyone curious about this social science.